Sandwich breakfast maker surface coating and preparation method thereof

By using surface coatings of materials such as silicone resin, nanoanti-anti-bacterial particles and modified silicon carbide on the hot plate of the sandwich breakfast machine, the problems of food adhesion and bacterial growth are solved, and better antibacterial and wear resistance are achieved, and the performance of the antibacterial and wear resistance is extended. Service life.

CN119144227APending Publication Date: 2024-12-17NINGBO GOLDEN AGE ELECTRIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411169769.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-25
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The hot plate of the sandwich breakfast machine is prone to adhesion of ingredients, which leads to bacterial growth and shortened service life.

Method used

Using a surface coating composed of silicone resin, nanoanti-anti-bacterial particles, modified silicon carbide and solvent, the nanoanti-anti-bacterial particles are Ag-CuO composite nanoparticles, enhanced by silica coating and carbon layer, combined with phenyl MQ silicone resin Doping with boron ions improves the antibacterial and mechanical properties of the coating.

Benefits of technology

It significantly improves the antibacterial properties and wear resistance of the surface coating of the sandwich breakfast machine, extends the service life, and avoids the adhesion of ingredients and bacterial growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005008929000000071
    Figure BDA0005008929000000071
  • Figure BDA0005008929000000091
    Figure BDA0005008929000000091
  • Figure BDA0005008929000000101
    Figure BDA0005008929000000101
Patent Text Reader

Abstract

The invention relates to the technical field of baking utensil surface coatings, in particular to a sandwich breakfast maker surface coating and a preparation method thereof. The invention discloses a surface coating of a sandwich breakfast maker. The surface coating comprises the following raw materials in parts by weight: 100-160 parts of organic silicon resin, 30-40 parts of nano antibacterial particles, 80-100 parts of modified silicon carbide, 1-6 parts of a dispersing agent and 20-40 parts of a solvent, and the nano antibacterial particles contain Ag-CuO composite nano particles. The surface coating of the sandwich breakfast maker has excellent antibacterial performance and mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of surface coatings for baking utensils, and more specifically, to a surface coating for a sandwich breakfast machine and a preparation method thereof. Background Art

[0002] As society continues to develop and progress, people's pace of life is getting faster and faster. Fast food is an inevitable choice in people's lives, and the same is true for breakfast. Among them, breakfast is the first meal to greet a day's work, and its importance is obvious. However, due to commuting, people usually treat breakfast carelessly. Sandwich breakfast machines can make sandwiches quickly, simply and effectively, thus effectively saving people the time needed to make breakfast.

[0003] The sandwich breakfast machine consists of two hot plates. When preparing a sandwich, you only need to sandwich the bread slices and the sandwich ingredients, and the two hot plates can heat and fry the ingredients until they are cooked. In order to obtain excellent heat conduction, the material of the hot plate is usually metal. After the metal hot plate is in direct contact with the ingredients and baked at high temperature, the ingredients are easily attached to the surface of the hot plate, thus affecting the normal use of the hot plate. At the same time, the attachment of the ingredients will also cause bacteria to grow.

[0004] Therefore, there is an urgent need for a non-stick coating with antibacterial properties to be applied to the hot plate surface of a sandwich breakfast machine. Summary of the invention

[0005] In order to improve the defect that the hot plate of a sandwich breakfast machine is easily attached to food, thereby causing bacterial growth, the present application provides a surface coating of a sandwich breakfast machine and a preparation method thereof.

[0006] In the first aspect, the present application provides a surface coating for a sandwich breakfast machine, which adopts the following technical solution:

[0007] A surface coating of a sandwich breakfast machine comprises the following raw materials in parts by weight: 100-160 parts of organic silicon resin, 30-40 parts of nano antibacterial particles, 80-100 parts of modified silicon carbide, 1-6 parts of dispersant and 20-40 parts of solvent; the nano antibacterial particles contain Ag-CuO composite nano particles.

[0008] Nanosilver is a common spectrum antibacterial agent with good biocompatibility. It can inhibit the growth of many bacteria and does not produce drug resistance. Nano copper oxide can destroy bacterial cell membranes, damage DNA, inhibit protein synthesis and block different biological pathways. Compared with nano silver and nano copper oxide, Ag-CuO composite nanoparticles have better antibacterial properties. The reason is that Ag and CuO have a synergistic effect, which can promote the growth of bacteria under the action of light irradiation. 1 O2 generation and release of Ag ions.

[0009] Preferably, the antibacterial nanoparticles are Ag-CuO composite nanoparticles coated with silica.

[0010] Metal nanoparticles have a certain agglomeration effect, and the poor dispersion caused by agglomeration can easily inhibit their excellent antibacterial properties. Silicon dioxide has excellent biocompatibility. When silicon dioxide is coated on the surface of Ag-CuO composite metal, it can load the Ag-CuO composite metal, reduce the aggregation of metal nanoparticles, and promote the nano antibacterial particles to achieve a long-lasting antibacterial effect through sustained release.

[0011] Preferably, the method for preparing the nano antibacterial particles comprises the following steps:

[0012] S1. At room temperature, add Ag nanoparticles to the PVP aqueous solution and mix them evenly, then add Cu(NO3)2·3H2O and HMTA and mix and stir, and then react at a temperature of 90-100°C for 1-3h to obtain an Ag-CuO composite metal salt solution;

[0013] S2, dispersing APTES in anhydrous ethanol, then adding Ag-CuO composite metal salt solution to mix evenly, and then adding nitric acid to shake and stir to obtain a precursor solution;

[0014] S3. Atomize the precursor solution into tiny aerosol droplets, and then transfer the aerosol droplets to a tubular furnace at 600°C through a mixed carrier gas. The mixed carrier gas is a mixture of nitrogen and hydrogen, and the carrier gas pressure is 0.2MPa. After that, the aerosol droplets undergo evaporation, crystallization, pyrolysis, and sintering operations, and are then cooled and diluted with nitrogen to obtain silica-coated Ag-CuO composite nanoparticles solid powder, i.e., nano antibacterial particles.

[0015] Preferably, in S1, the volume ratio of Ag nanoparticles, PVP aqueous solution, Cu(NO3)2·3H2O and HMTA is 1:(10-12):(0.2-0.3):(0.2-0.3);

[0016] In S2, the mass ratio of APTES, anhydrous ethanol and Ag-CuO composite metal salt solution is (4-6):(10-14):(1-2).

[0017] When the nano antibacterial particles are prepared by the above method and the above ratio is selected, the prepared nano antibacterial particles have better antibacterial properties.

[0018] Preferably, the modified silicon carbide is silicon carbide reinforced by carbon coating-coated silicon carbide nanowires, and the preparation method of the modified silicon carbide is:

[0019] A1. First, a phenolic resin coating is uniformly coated on the surface of the silicon carbide nanowires, and then ball milling, dispersion and drying are performed to obtain a modified silicon carbide nanowire pre-material;

[0020] A2. Mix and dry the modified silicon carbide nanowire preparation, silicon carbide powder, sintering aid and anhydrous ethanol in a mass ratio of 6:10:1:2, and then perform an anaerobic heat treatment. The anaerobic heat treatment operation is to keep warm at 350°C for 2 hours and 650°C for 2 hours to carbonize the phenolic resin coating, and then perform a sintering treatment at a sintering temperature of 1800°C to obtain silicon carbide reinforced with carbon coating coated silicon carbide nanowires.

[0021] Silicone resin has excellent non-stick properties, so it can be used as a surface coating for sandwich breakfast machines, but its mechanical properties are low, its wear resistance is poor, and its service life is short. Silicon carbide has the advantages of high strength, high thermal shock resistance, high wear resistance and low expansion coefficient, so when silicon carbide is added to the silicone coating system, the prepared silicone coating will also have excellent mechanical properties.

[0022] However, the toughness of silicon carbide is poor, while silicon carbide nanowires, as a one-dimensional material, not only have various superior mechanical properties similar to those of silicon carbide matrix, but also have excellent toughness. However, since silicon carbide nanowires belong to β-SiC and silicon carbide matrix belongs to α-SiC, the two have similar properties, so it is easy to make the interface bonding between the two too strong during sintering. This will not only damage the silicon carbide nanowires, but also make the silicon carbide nanowires unable to absorb the fracture energy through the pull-out and bridging mechanism when cracks occur in the matrix, and the effect of improving the mechanical properties of the matrix is ​​limited.

[0023] When the surface of silicon carbide nanowires is coated with a carbon layer, the carbon layer can effectively avoid an excessively strong interface structure between the nanowires and the matrix, thereby achieving a reinforcement and toughening effect.

[0024] Preferably, the surface coating of the sandwich breakfast machine further comprises 20-60 parts of modified phenyl MQ silicone resin.

[0025] Preferably, the modified phenyl MQ silicone resin is doped with boron ions.

[0026] Phenyl MQ silicate has the effect of increasing the hardness and wear resistance of the silicone coating, while the doping of boron ions can form a SiO2-B2O3 precursor hybrid cross-linked network containing Si-OB bonds in the silicone coating, thereby effectively improving the mechanical properties of the silicone surface coating.

[0027] Preferably, the preparation method of the modified phenyl MQ silicone resin comprises the following steps:

[0028] B1. First, phenyldimethylethoxysilane and boric acid are heated and mixed in a mass ratio of 3:1 at 95°C for 20 min and 170°C for 40 min to obtain a borosilicate matrix;

[0029] B2. Mix ethanol, water and tetramethylammonium hydroxide, and then gradually add a mixture of tetraethyl orthosilicate, hexamethyldisiloxane and borosilicate matrix, the mass ratio of tetraethyl orthosilicate, hexamethyldisiloxane and borosilicate matrix is ​​6:1:3. After the addition is completed, react at 30°C for 2h, then heat to 65°C and continue to react for 5h, finally wash, extract and dry to obtain modified phenyl MQ silicone resin.

[0030] In a second aspect, the present application provides a method for preparing a surface coating of a sandwich breakfast machine, using the following technical solution:

[0031] A method for preparing a surface coating of a sandwich breakfast machine comprises the following steps: mixing organic silicon resin, nano antibacterial particles, modified silicon carbide, a dispersant and a solvent at a mixing speed of 150-200 r / min, a mixing time of 120-150 min and a mixing temperature of 90-100° C. to obtain the surface coating of the sandwich breakfast machine.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. Compared with nanosilver and nanocopper oxide, Ag and CuO have a synergistic effect, which can promote the generation of 1O2 and the release of Ag ions under the action of light irradiation, making Ag-CuO composite nanoparticles have better antibacterial properties.

[0034] 2. Metal nanoparticles have a certain agglomeration effect, and the poor dispersion caused by agglomeration can easily lead to the inhibition of their excellent antibacterial properties. Silica has excellent biocompatibility. When silica is coated on the surface of Ag-CuO composite metal, silica can load the Ag-CuO composite metal, reduce the aggregation of metal nanoparticles, and promote the nano antibacterial particles to achieve a long-lasting antibacterial effect through sustained release.

[0035] 3. Silicon carbide can improve the mechanical properties of silicone coatings, silicon carbide nanowires can improve the toughness of silicone coatings, and the carbon layer can effectively avoid an excessively strong interface structure between the nanowires and the substrate, thereby achieving a reinforcing and toughening effect.

[0036] 4. Phenyl MQ silicate has the effect of increasing the hardness and wear resistance of the silicone coating, and the doping of boron ions can form a SiO2-B2O3 precursor hybrid cross-linking network containing Si-OB bonds in the silicone coating, thereby effectively improving the mechanical properties of the silicone surface coating. DETAILED DESCRIPTION

[0037] The present application is further described in detail below in conjunction with Examples 1-10 and Comparative Examples 1-4.

[0038] raw material

[0039] Silicone resin monomer - triacetoxyethylsilane CAS: 17689-77-9; dispersant - polyacrylate CAS: 107-10-8; solvent - butyl acetate CAS: 123-86-4; nano silver Beijing October New Materials; nano copper oxide Hangzhou Hengna New Materials; PVP CAS: 9003-39-8; Cu(NO3)2·3H2O CAS: 10031-43-3; HMTA CAS: 100-97-0; APTES CAS: 919-30-2; ethanol CAS: 64-17-5; nitric acid CAS: 7697-37-2; silicon carbide nanowire Angxing new carbon material; phenolic resin Shangwei 901 resin; sintering aid Ganzhou Tejing New Material Y2O3; phenyl dimethyl ethoxy silane CAS: 78-62-6; boric acid CAS: 10043-35-3; tetramethyl ammonium hydroxide CAS: 75-59-2; tetraethyl orthosilicate CAS: 78-10-4; hexamethyldisiloxane CAS: 107-46-0.

[0040] Example

[0041] Example 1

[0042] A surface coating for a sandwich breakfast machine comprises the following raw materials: 140 g of organic silicon resin, 35 g of nano antibacterial particles, 90 g of silicon carbide, 3.5 g of a dispersant and 30 g of a solvent.

[0043] The preparation method of the surface coating of the sandwich breakfast machine is as follows: organic silicon resin, nano antibacterial particles, modified silicon carbide, dispersant and solvent are mixed at a mixing speed of 180r / min, a mixing time of 140min and a mixing temperature of 95°C to obtain the surface coating of the sandwich breakfast machine.

[0044] Among them, the nano-antibacterial particles are Ag-CuO composite nanoparticles. The preparation method of Ag-CuO composite nanoparticles is: at room temperature, 1 ml of Ag nanoparticles is added to 11.5 ml of PVP aqueous solution (Mw=40000, monomer concentration 110 mM) and mixed evenly, and then 0.25 ml of Cu(NO3)2·3H2O and 0.25 ml of HMTA are added for mixing and stirring, and then reacted at a temperature of 95°C for 2 hours, and the reactants were collected by centrifugation at 7500r / min for 15 minutes, washed, dispersed and dried to obtain Ag-CuO composite nanoparticles.

[0045] Example 2

[0046] The difference from Example 1 is that the antibacterial nanoparticles are Ag-CuO composite nanoparticles coated with silica;

[0047] The preparation method of silica-coated Ag-CuO composite nanoparticles comprises the following steps:

[0048] S1. At room temperature, 1 ml of Ag nanoparticles was added to 11.5 ml of PVP aqueous solution (Mw = 40000, monomer concentration 110 mM) and mixed evenly, and then 0.25 ml of Cu(NO3)2·3H2O and 0.25 ml of HMTA were added for mixing and stirring, and then reacted at 95°C for 2 h to obtain a Ag-CuO composite metal salt solution;

[0049] S2, dispersing 5g of APTES in 12g of anhydrous ethanol, then adding 1.5g of Ag-CuO composite metal salt solution and mixing evenly, then adding 0.09g of nitric acid and shaking and stirring to obtain a precursor solution;

[0050] S3. Atomize the precursor solution into tiny aerosol droplets, and then transfer the aerosol droplets to a tubular furnace at 600°C through a mixed carrier gas. The mixed carrier gas is a mixture of nitrogen and hydrogen, and the carrier gas pressure is 0.2MPa. After that, the aerosol droplets undergo evaporation, crystallization, pyrolysis, and sintering operations, and are then cooled and diluted with nitrogen to obtain silica-coated Ag-CuO composite nanoparticles solid powder, i.e., nano antibacterial particles.

[0051] Embodiment 3-4

[0052] The difference from Example 2 is that the added amounts of the various components of the nano antibacterial particles are different, as shown in Table 1.

[0053] Table 1 Addition amount of each component of nano antibacterial particles in Examples 2-4

[0054]

[0055] Example 5

[0056] The difference from Example 2 is that silicon carbide is replaced by modified silicon carbide with the same addition amount, and the modified silicon carbide is silicon carbide reinforced with silicon carbide nanowires;

[0057] The preparation method of silicon carbide reinforced by silicon carbide nanowires is as follows: 90g of silicon carbide nanowires, 100g of silicon carbide powder, 10g of a sintering aid and 20g of anhydrous ethanol are mixed and dried, and then sintered at a sintering temperature of 1800°C to obtain silicon carbide reinforced by silicon carbide nanowires.

[0058] Example 6

[0059] The difference from Example 2 is that the modified silicon carbide is silicon carbide reinforced by carbon coating-coated silicon carbide nanowires;

[0060] The method for preparing carbon coating-coated silicon carbide nanowire-enhanced silicon carbide comprises the following steps:

[0061] A1. First, a layer of phenolic resin coating is uniformly coated on the surface of silicon carbide nanowires, and the mass ratio of silicon carbide nanowires to phenolic resin is 3:1. Then, ball milling, dispersion and drying are performed to obtain a modified silicon carbide nanowire pre-material;

[0062] A2. Mix and dry 90g of silicon carbide nanowire modified preparation, 100g of silicon carbide powder, 10g of sintering aid and 20g of anhydrous ethanol, and then perform anaerobic heat treatment. The anaerobic heat treatment operation is to keep warm at 350°C for 2h and 650°C for 2h to carbonize the phenolic resin coating, and then perform sintering treatment at a sintering temperature of 1800°C to obtain silicon carbide reinforced with silicon carbide nanowires.

[0063] Example 7

[0064] The difference from Example 6 is that 40 g of phenyl MQ silicone resin is also added to the surface coating of the sandwich breakfast machine;

[0065] The preparation method of phenyl MQ silicone resin is as follows: 200 ml of ethanol, 400 ml of water and 100 ml of tetramethylammonium hydroxide are mixed, and then a mixed solution of 60 g of ethyl orthosilicate, 10 g of hexamethyldisiloxane and 30 g of phenyldimethylethoxysilane is gradually added dropwise, and after the addition is completed, the mixture is reacted at 30° C. for 2 h, and then the temperature is raised to 65° C. and the reaction is continued for 5 h, and finally the mixture is washed, extracted and dried to obtain phenyl MQ silicone resin.

[0066] Example 8

[0067] The difference from Example 7 is that the phenyl MQ silicone resin is doped with boron ions;

[0068] The preparation method of the phenyl MQ silicone resin doped with boron ions comprises the following steps:

[0069] B1. First, 30 g of phenyldimethylethoxysilane and 10 g of boric acid were heated and mixed at 95° C. for 20 min and 170° C. for 40 min to obtain a borosilicate matrix;

[0070] B2. Mix 200 ml of ethanol, 400 ml of water and 100 ml of tetramethylammonium hydroxide, then gradually add a mixture of 60 g of ethyl orthosilicate, 10 g of hexamethyldisiloxane and 30 g of borosilicate matrix. After the addition is complete, react at 30°C for 2 hours, then heat to 65°C and continue to react for 5 hours. Finally, wash, extract and dry to obtain phenyl MQ silicone resin.

[0071] Examples 9-10

[0072] The difference from Example 8 is that the added amounts of the components of the surface coating of the sandwich breakfast machine are different, as shown in Table 2.

[0073] Table 2 Addition amount of each component of the surface coating of the sandwich breakfast machine in Examples 8-10 / g

[0074]

[0075] Comparative Example

[0076] Comparative Example 1

[0077] The difference from Example 1 is that no antibacterial nanoparticles are added.

[0078] Comparative Example 2

[0079] The difference from Example 1 is that the Ag-CuO composite nanoparticles are replaced with the same amount of nanosilver added.

[0080] Comparative Example 3

[0081] The difference from Example 1 is that the Ag-CuO composite nanoparticles are replaced by nano copper oxide with the same added amount.

[0082] Comparative Example 4

[0083] The difference from Example 2 is that silicon carbide is no longer added.

[0084] Performance testing

[0085] Detection Methods

[0086] Sample preparation: Six samples were taken from Examples 1-10 and Comparative Examples 1-4, and then sprayed on a hot plate substrate by air spraying. The spraying process parameters were: spray gun diameter 1.0 mm, spraying pressure 0.2 MPa, spraying distance 20 cm, spraying thickness 20 μm. After spraying, baking was performed at a baking temperature of 280° C. and a baking time of 10 min.

[0087] 1. Antibacterial performance test

[0088] Three samples were selected from Examples 1-4 and Comparative Examples 1-3, and then antibacterial tests were performed on the samples according to QB / T 2591-2003 "Test Methods and Antibacterial Effects of Antibacterial Plastics" to obtain the antibacterial rates and take the average values. The experimental data are shown in Table 3.

[0089] 2. Wear resistance test

[0090] Three samples were selected from Example 2, Examples 5-10 and Comparative Example 4, and the initial mass M0 of the samples was measured.

[0091] Subsequently, referring to GB / T1768-2006 "Determination of wear resistance of paints and varnishes - Rotating rubber grinding wheel method", the above samples were subjected to a 1000r friction test, and the post-test mass M1 of the sample was recorded. Finally, the wear resistance was characterized by the wear amount, wear amount = M0-M1, and the results were averaged. The experimental data are shown in Table 3.

[0092] Table 3 Test data table of Examples 1-10 and Comparative Examples 1-3

[0093]

[0094]

[0095] With reference to Comparative Examples 1-3 and Example 1 and in combination with Table 3, it can be seen that the antibacterial properties of Comparative Examples 2-3 are significantly improved compared with Comparative Example 1, which shows that both nano-silver and nano-copper oxide have excellent antibacterial properties.

[0096] Among them, nanosilver is a common spectrum antibacterial agent with good biocompatibility, which can inhibit the growth of many bacteria and does not produce drug resistance. Nano copper oxide can destroy bacterial cell membranes, damage DNA, inhibit protein synthesis and block different biological pathways.

[0097] Compared with Comparative Examples 2-3, the antibacterial rate of Example 1 is further improved, which shows that compared with nano-silver and nano-copper oxide, Ag-CuO composite nanoparticles have better antibacterial properties. The reason is that Ag and CuO have a synergistic effect, which can promote the antibacterial activity under the action of light irradiation. 1 O2 generation and release of Ag ions.

[0098] Referring to Examples 1-2 and in combination with Table 3, it can be seen that, relative to Example 1, the antibacterial rate of Example 2 is further improved, which indicates that the coating of silica can further improve the antibacterial properties of Ag-CuO composite nanoparticles.

[0099] The reason is that metal nanoparticles have a certain agglomeration effect, and the poor dispersion caused by agglomeration can easily inhibit their excellent antibacterial properties. Silicon dioxide has excellent biocompatibility. When silicon dioxide is coated on the surface of Ag-CuO composite metal, it can load the Ag-CuO composite metal, reduce the aggregation of metal nanoparticles, and promote the nano antibacterial particles to achieve a long-lasting antibacterial effect through sustained release.

[0100] Referring to Examples 2-4 and in combination with Table 3, it can be seen that, relative to Example 2, the antibacterial rates of Examples 3-4 are relatively low, which indicates that when the components of the nano-antibacterial particles are formulated in the same proportion as in Example 2, the prepared surface coating of the sandwich breakfast machine will have better antibacterial properties.

[0101] Referring to Example 2 and Comparative Example 4 and in combination with Table 3, it can be seen that the wear resistance of Example 2 is significantly improved compared with Comparative Example 4. The reason for this is that the silicone resin has excellent non-stick properties, so it can be used as a surface coating for a sandwich breakfast machine, but its mechanical properties are relatively low, its wear resistance is relatively poor, and its service life is relatively short. Silicon carbide has the advantages of high strength, high thermal shock resistance, high wear resistance, and low expansion coefficient. Therefore, when silicon carbide is added to the silicone coating system, the prepared silicone coating will also obtain excellent mechanical properties.

[0102] Referring to Example 2 and Example 5 and combining with Table 3, it can be seen that the wear resistance of Example 5 is further improved compared with Example 2, which shows that the addition of silicon carbide nanowires can further enhance the wear resistance of the surface coating of the sandwich breakfast machine. The reason is that the toughness of silicon carbide material is poor, and silicon carbide nanowires, as a one-dimensional material, not only have various superior mechanical properties similar to silicon carbide matrix, but also have excellent toughness, thereby further improving its wear resistance.

[0103] Referring to Examples 5-6 and in combination with Table 3, it can be seen that compared with Example 5, the wear resistance of Example 6 is further improved, which indicates that coating the surface of silicon carbide nanowires with a carbon coating can further improve the wear resistance of the surface coating of the sandwich breakfast machine.

[0104] The reason is that silicon carbide nanowires belong to β-SiC and silicon carbide matrix belongs to α-SiC. The two have similar properties, so it is easy to make the interface bonding between the two too strong during sintering. This will not only damage the silicon carbide nanowires, but also make the silicon carbide nanowires unable to absorb the fracture energy through the pull-out and bridging mechanism when cracks appear in the matrix, and the mechanical properties of the matrix will be limited. When the surface of the silicon carbide nanowire is coated with a carbon layer, the carbon layer can effectively avoid an excessively strong interface structure between the nanowire and the matrix, thereby achieving a reinforcement and toughening effect.

[0105] With reference to Examples 6-8 and in combination with Table 3, it can be seen that, relative to Example 6, the wear resistance of Example 7 is further improved, which indicates that phenyl MQ silicate has the effect of increasing the hardness and wear resistance of the silicone coating.

[0106] Compared with Example 7, the wear resistance of Example 8 is further improved, which shows that the doping of boron ions can further improve the wear resistance of the surface coating of the sandwich breakfast machine. The reason is that the doping of boron ions can form a SiO2-B2O3 precursor hybrid cross-linked network containing Si-OB bonds in the organic silicon coating, thereby effectively improving the mechanical properties of the organic silicon surface coating.

[0107] With reference to Examples 8-10 and in combination with Table 3, it can be seen that, relative to Example 8, the wear resistance of Examples 9-10 is slightly reduced, which indicates that when the components of the surface coating of the sandwich breakfast machine adopt the proportions of Example 8, the prepared surface coating of the sandwich breakfast machine will have better wear resistance.

[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A surface coating for a sandwich breakfast machine, characterized in that: The invention comprises the following raw materials in parts by weight: 100-160 parts of organic silicon resin, 30-40 parts of nano antibacterial particles, 80-100 parts of modified silicon carbide, 1-6 parts of dispersant and 20-40 parts of solvent; the nano antibacterial particles contain Ag-CuO composite nano particles.

2. The surface coating of the sandwich breakfast machine according to claim 1, characterized in that: The antibacterial nanoparticles are Ag-CuO composite nanoparticles coated with silicon dioxide.

3. The surface coating of the sandwich breakfast machine according to claim 2, characterized in that: The preparation method of the nano antibacterial particles comprises the following steps: S1. At room temperature, add Ag nanoparticles to the PVP aqueous solution and mix them evenly, then add Cu(NO3)2·3H2O and HMTA and mix and stir, and then react at a temperature of 90-100°C for 1-3h to obtain an Ag-CuO composite metal salt solution; S2, dispersing APTES in anhydrous ethanol, then adding Ag-CuO composite metal salt solution to mix evenly, and then adding nitric acid to shake and stir to obtain a precursor solution; S3. Atomize the precursor solution into tiny aerosol droplets, and then transfer the aerosol droplets to a tubular furnace at 600°C through a mixed carrier gas. The mixed carrier gas is a mixture of nitrogen and hydrogen, and the carrier gas pressure is 0.2MPa. After that, the aerosol droplets undergo evaporation, crystallization, pyrolysis, and sintering operations, and are then cooled and diluted with nitrogen to obtain silica-coated Ag-CuO composite nanoparticles solid powder, i.e., nano antibacterial particles.

4. The surface coating of the sandwich breakfast machine according to claim 3, characterized in that: In S1, the volume ratio of Ag nanoparticles, PVP aqueous solution, Cu(NO3)2·3H2O and HMTA is 1:(10-12):(0.2-0.3):(0.2-0.3); in S2, the mass ratio of APTES, anhydrous ethanol and Ag-CuO composite metal salt solution is (4-6):(10-14):(1-2).

5. The surface coating of the sandwich breakfast machine according to claim 1, characterized in that: The modified silicon carbide is silicon carbide reinforced by carbon coating-coated silicon carbide nanowires, and the preparation method of the modified silicon carbide is: A1. First, a phenolic resin coating is uniformly coated on the surface of the silicon carbide nanowires, and then ball milling, dispersion and drying are performed to obtain a modified silicon carbide nanowire pre-material; A2. Mix and dry the modified silicon carbide nanowire preparation, silicon carbide powder, sintering aid and anhydrous ethanol in a mass ratio of 6:10:1:2, and then perform an anaerobic heat treatment. The anaerobic heat treatment operation is to keep warm at 350°C for 2 hours and 650°C for 2 hours to carbonize the phenolic resin coating, and then perform a sintering treatment at a sintering temperature of 1800°C to obtain silicon carbide reinforced with carbon coating coated silicon carbide nanowires.

6. The surface coating of the sandwich breakfast machine according to claim 1, characterized in that: The surface coating of the sandwich breakfast machine also includes 20-60 parts of modified phenyl MQ silicone resin.

7. The surface coating of the breakfast sandwich machine according to claim 6, characterized in that: The modified phenyl MQ silicone resin is doped with boron ions.

8. The surface coating of the breakfast sandwich machine according to claim 7, characterized in that: The preparation method of modified phenyl MQ silicone resin comprises the following steps: B1. First, phenyldimethylethoxysilane and boric acid are heated and mixed in a mass ratio of 3:1 at 95°C for 20 min and 170°C for 40 min to obtain a borosilicate matrix; B2. Mix ethanol, water and tetramethylammonium hydroxide, and then gradually add a mixture of tetraethyl orthosilicate, hexamethyldisiloxane and borosilicate matrix, the mass ratio of tetraethyl orthosilicate, hexamethyldisiloxane and borosilicate matrix is ​​6:1:

3. After the addition is completed, react at 30°C for 2h, then heat to 65°C and continue to react for 5h, finally wash, extract and dry to obtain modified phenyl MQ silicone resin.

9. A method for preparing a surface coating of a sandwich breakfast machine according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing organic silicon resin, nano antibacterial particles, modified silicon carbide, dispersant and solvent at a mixing speed of 150-200 r / min, a mixing time of 120-150 min and a mixing temperature of 90-100 DEG C to obtain a surface coating of a sandwich breakfast machine.